Acoustic-Perceptual Factors Both Maintain and Account for the Rarity of the Czech Trill-Fricative - Howson, Phil J.; Monahan, Philip J. (Frontiers in Communication, 2022)
Czech has a sibilant inventory that contrasts at three places of articulation: alveolar, a pre-post-alveolar, and palato-alveolar. The specific aim of this study is to examine the perception of the typologically rare Czech sibilant inventory and to determine whether acoustic-perceptual characteristics play a role in the maintenance of the Czech trill-fricative. These results are compared to a more common three-way sibilant inventory, Polish. Native Czech listeners performed an auditory AX discrimination task in two blocks: a Czech block and a Polish block. Stimuli were embedded in varying levels of noise to increase task difficulty. Signal-to-noise ratio differences affected the perception of the Czech sibilants more than Polish sibilants. Moreover, a multidimensional scaling analysis revealed less perceptual dispersion for the Czech inventory than the Polish inventory. These results suggest that there is greater difficulty maintaining the Czech inventory considering the signal-to-noise comparisons and that this a factor that contributes to its rarity; however, similarities in perceptual dispersion indicate that maintenance across several acoustic-perceptual cues is possible, and Czech shows few signs of losing this typologically rare contrast.